How is Innovation fostered under different Institutional Setup: Comparing the Electronics Cluster in Shenzhen and Dongguan, China - Wenying Fu (European Regional Science Association (ERSA), 2011)
The primary focus of this paper is to provide empirical evidence on how innovation is generated and fostered under different institutional setup. Two different institutional setups which evolve from planned economy to market economy in China during the transition, i.e. top-down and bottom-up institutions to promote industrial development, are discussed in the context of our study area, i.e. Dongguan and Shenzhen in Pearl River Delta, China. Drawing on the firm survey data collected in the electronics industry of Dongguan and Shenzhen, this paper explores the factors that foster the innovation activities respectively under these two different institutional setups. The results shows that the flexible institutions organized from bottom up targeting at attracting process trade, which is dominant in Dongguan, restricts the scope of interaction and learning related to innovation and would probably lock-in the city in low-end production activities if the existing institutional setup cannot be broken up. On the other hand, institutional setup favoring the agglomeration of knowledge-related and knowledge-intensive institutes and ex-ante strategic support organized from top down in Shenzhen economic special zone contributes to the reciprocal and systematic interaction between firms as well as knowledge institutions. Finally, policy implication is further discussed by comparing the territorial innovation system in Europe and America where innovation institutions are mature, concluding that the capacity of public and private institutions should be strengthened to form the stable systematic interaction to foster innovation in the long run.
Keywords: 330